Bent out of shape: The impact of deviating heart morphology on cardiac function in Atlantic salmon (Salmo salar L.) - Victoria Becker; Simona Kavaliauskiene; Daniel Morgenroth; Sudip Mahat; William E. Louch; Ida B. Johansen; Michael Frisk (Aquaculture, 2026)

Insectivores exhibit superior microbial network connectivity and elevated zoonotic risk by 2035 relative to rodents and bats - Hongfeng Li; Zheng Y. X. Huang; Jie Lan; Li Hu; Zhilin Wang; Yingying Wang; Luca Santini; Daniel J. Becker; Yifei Xu (Science China Life Sciences, 2026)

Longitudinal Impacts of Forest Loss on Bartonella and Hemotropic Mycoplasma Dynamics in Vampire Bats Within a Fragmented Habitat - Lauren R. Lock; Kristin E. Dyer; Dmitriy V. Volokhov; Anni Yang; M. Brock Fenton; Nancy B. Simmons; Daniel J. Becker (Molecular Ecology, 2026)
Habitat fragmentation can negatively impact wildlife, including increasing infectious disease risk. We assessed spatiotemporal changes in pathogen dynamics in vampire bats ( Desmodus rotundus ) in response to habitat fragmentation using general linear mixed models to investigate the influence of site, year, and tree cover on Bartonella spp. and hemotropic Mycoplasma spp. (hemoplasmas) infection risk in bats in one large and one small forest fragment in Belize across seven years. While Bartonella infections were more likely in the final years of the study regardless of site, hemoplasma infection likelihood was not significantly different across years or sites. Bartonella infections were associated with increased forest loss in the large fragment only, whereas hemoplasma infections were not associated with forest loss. The effects of site, year, and forest loss on infection likelihood varied by pathogen genotype despite low model explanatory power. Neither site nor year was associated with bartonellae, but one genotype was positively associated with tree cover. Two hemoplasmas were influenced by year with differing trends: one genotype was negatively associated with tree loss across sites, while another was positively associated with forest loss at the small fragment only. Both pathogens were similarly influenced by bat demographics and showed instances of infection status and genotype switching. Our work suggests that the effects of habitat fragmentation on infection risk depend on both the pathogen and specific genotype, complicating expectations of how environmental change affects wildlife disease dynamics. Efforts to mitigate infectious disease impacts in fragmented systems should be tailored to specific pathogens of concern.

The influence of egg incubation and rearing temperature on heart morphology and function in farmed Atlantic salmon (Salmo salar) - Pia Skovholt Halvorsen; Sudip Mahat; Simen W. Larsen; Tuva M.G. Sørgaard; Victoria Becker; Daniel Morgenroth; Morten Strøm; Marit Stormoen; William E. Louch; Simona Kavaliauskiene; Ida B. Johansen; Michael Frisk (Aquaculture, 2026)

Functional and structural cardiac remodelling in farmed Atlantic salmon (Salmo salar) - Pia Skovholt Halvorsen; Sudip Mahat; Victoria Becker; Simona Kavaliauskiene; Tuva M.G. Sørgaard; Daniel Morgenroth; Morten Strøm; William E. Louch; Ida B. Johansen; Michael Frisk (Aquaculture, 2026)

Virus‐Dependent Geographic Structure of Co‐Circulating Viruses in a Single Bat Species - Avery L. Holmes; Alice Broos; Daniel J. Becker; Jorge E. Carrera; Maxwell J. Farrell; Rita Ribeiro; Carlos Tello; Laura M. Bergner; Daniel G. Streicker (Molecular Ecology, 2026)
Understanding the spatial spread of viruses within wildlife populations is often a key component of disease management efforts. Viral spread is likely constrained by host ecology, but inter‐virus differences in infection strategy might allow some viruses to overcome these constraints, leading to divergent population structures within a common host environment. We studied the phylogeographic structure of six virus taxa (dependoparvovirus, deltavirus, mastadenovirus, betaherpesvirus and two lineages of rabies virus) circulating in common vampire bats ( Desmodus rotundus ) in Peru, finding that viral population structure is inconsistently constrained by host ecology. Specifically, while bat travel distance structured the genetic diversity of betaherpesvirus and two lineages of rabies virus, other viruses were instead constrained by anthropogenic factors (dependoparvovirus), or had weakly defined population structure (mastadenovirus). The genetic structure of all viruses was affected by a measure of human travel difficulty between sites, but effects varied in size and direction. Distinct drivers of viral population structure within the same host species imply that virus infection strategy can outweigh host ecological connectivity, acting as a key determinant of geographic spread. Because barriers to gene flow generalise poorly between viruses, whether a tractable virus can illuminate host population structure or predict the spread of high‐impact viruses depends on individual virus biology.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

A general framework for modeling pathogen transmission in co‐roosting host communities - Molly C. Simonis; Daniel J. Becker (Ecology, 2026)
Cross‐species transmission of pathogens can be facilitated by frequent contact among wildlife. Cross‐species transmission is often driven by phylogenetic similarity between host species, but the role this plays when multiple host species co‐roost is unknown. We developed a generalizable framework for understanding how cross‐species transmission is driven by contact among co‐roosting species spanning evolutionary similarities and the net impact on roost‐level infection prevalence. We developed ordinary differential equation models describing population and infection dynamics between two and three co‐roosting species. We derived conditions for pathogen invasion and parameterized models using co‐roosting Neotropical bat systems, with interspecific transmission exponentially declining with phylogenetic distance. To assess the relative contribution of contact rates and phylogenetic similarity, we co‐varied intraspecific transmission rates and phylogenetic distances while considering sensitivity to epidemiological structure and pathogen traits. For both susceptible–infected–recovered–susceptible and susceptible–infected–latent–infected models, we show that relatedness between co‐roosting hosts facilitates pathogen invasion, particularly for poorly transmissible pathogens with short durations of infection and immunity or latency. These models converged on similar equilibria, and roost‐level prevalence was greatest when hosts were most closely related. However, we also identified regions of parameter space where roost‐level prevalence increased when hosts were distantly related. Our generalizable models are adaptable to other co‐roosting systems with low‐virulence pathogens that are directly transmitted and inform our understanding of pathogen spillover.

Hunting, non-timber forestry products, and jaguars (Panthera onca): How livelihoods influence views toward jaguars in protected areas of the Bolivian Amazon - Andre Becker; Nuno Negrões; María Díez-León; Indyra Lafuente-Cartagena; Nelly Guerra; Daniel Larrea-Alcázar; Valeria Boron; Melissa Arias; Lila Sainz; Michelle Peñaranda; Bernarda Sanabria; Jenny Anne Glikman (Journal for Nature Conservation, 2026)

Production and applications of Bacillus sp. CL14 crude protease: approaches for biomass valorization and silver recovery - Gabriela Poll Moraes; Juliano Backes Scherer; Carolina Becker da Silva; Rafael Franco Pires; Daniel Joner Daroit (Systems Microbiology and Biomanufacturing, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Using acoustic telemetry to inform standardisation of catch rates from passive fishing gear: A case study using dusky flathead (Platycephalus fuscus) - Hayden T. Schilling; James A. Smith; Daniel E. Hewitt; Alistair Becker; Charles Gray; Geoffrey Liggins; Nicholas L. Payne; Dylan van der Meulen; Matthew D. Taylor (Fisheries Research, 2025)

Palynology, palynofacies and palaeoenvironment of the Serpukhovian Tazlourt Formation (Tinghir region, southern margin of the Variscan Zone, SE Morocco) - Amine Talih; Daniel Ţabără; Hamid Slimani; Ralph Thomas Becker; Imad Tmimne; Salma Aboutofail; Hicham El Asmi; Soukaina Jaydawi (Review of Palaeobotany and Palynology, 2025)

A paired analysis of mercury among non-invasive tissues in Mexican free-tailed bats (Tadarida brasiliensis) to inform conservation monitoring - Molly C. Simonis; Kimberlee Whitmore; Kristin E. Dyer; Meagan Allira; Bret Demory; Matthew M. Chumchal; Daniel J. Becker (Ecotoxicology, 2025)
Contaminants can harm wildlife. However, measuring wildlife exposure to contaminants can be challenging due to accessibility of species and/or sampling tissue matrices needed to assess wildlife health risks. For example, in bats and other taxa that use roosts, collecting feces under colonies minimizes disturbance to species of conservation concern, but fecal contaminant concentrations may not directly correlate with tissue contaminant concentrations. Thus, there is a need for quantifying contaminant exposure relationships between sample matrices for initial risk assessments to address wildlife health and conservation needs. Our goal was to assess the relationship between fecal and fur total mercury (THg) concentrations. We collected paired feces and fur samples ( n = 48) from Mexican free-tailed bats ( Tadarida brasiliensis ) in summer 2023 in western Oklahoma at a maternity roost. At the individual level, we found no correlation between fecal and fur THg. However, at the population level, fur THg concentrations were on average 6.06-times greater than fecal THg concentrations. We conclude that although fecal THg cannot serve as a proxy of individual bat fur THg, population-level differences could be used cautiously to estimate mean fur THg concentrations from under-roost feces and motivate individual-level sampling to assess health impacts. We encourage continued research across other insectivorous bat species and sites for determining THg relationships across tissues and initial risk assessments with minimal disturbance to species of conservation concern when a contaminant point source is not yet known.

Perspective article: Multisectoral considerations to enable a circular economy for plastics - Annika Jahnke; Aaron J. Beck; Richard L. Becker; Daria Bedulina; Ulrike Braun; Gunnar Gerdts; Lars Hildebrandt; Hanna Joerss; Ole Klein; Janine Korduan; Christian Laforsch; Gisela Lannig; et al. (Journal of Hazardous Materials, 2025)

Capture Probability of Blue Swimmer Crab ( Portunus armatus ) in Baited Traps and Implications for Trap Survey Design - Alistair Becker; Daniel D. Johnson; Hugh Pederson; Matthew D. Taylor (Fisheries Management and Ecology, 2025)
Fishery independent surveys provide valuable data for fisheries assessments that predominantly rely on trends in catch per unit effort (CPUE). Many crustacean fisheries are harvested using traps, so this gear is often used for fishery independent surveys. The areal sampling unit for baited traps is normally poorly understood, so surveys can be biased if sampling areas overlap. The blue swimmer crab ( Portunus armatus ) is an important commercial and recreational species distributed around the warm temperate and tropical coast of Australia, and stock management typically relies on catch data supplemented by independent surveys. Acoustic telemetry was used to track fine‐scale movements of 37 crabs in response to deployment of baited‐traps and to estimate probability of capture relative to distance from the trap. Traps attracted crabs from an initial distance up to 70 m, with most movements towards traps after dark. Capture probability increased with decreasing initial distance from a deployed trap. Despite this, the probability of capture was

Ichthyoplankton temporal and spatial patterns in sub-Antarctic coastal and oceanic waters of the Southwestern Atlantic - Daniel O. Bruno; Luciana Riccialdelli; Yamila Becker; Jacobo Martin; Mariela F. Victorio; Eduardo M. Acha; Daniel A. Fernández (Estuarine, Coastal and Shelf Science, 2025)

Conference Report: Cerebellar Development and Disease at Single-Cell Resolution - Lena M. Kutscher; Davide Aprile; N. Sumru Bayin; Esther B. E. Becker; Valentina Cerrato; Giacomo Turrini; Marion Coolen; Vincent Cantagrel; Béatrice C. Durand; Myron K. Evans II; Parthiv Haldipur; Kathleen J. Millen; et al. (The Cerebellum, 2025)

New insights into methylfuran metabolism - Daniel Bohlen; Jonas Appel; Lukas Eichel; Samuel Spengler; Carolin Kulosa; Fani Kougioumtzi; Simone Stegmüller; Nico Becker; Tobias Jochum; Elke Richling (Toxicology Letters, 2025)

Experimental Drought Suppresses Amphibian Pathogen Yet Intensifies Transmission and Disrupts Protective Skin Microbiome - Shannon Buttimer; Daniel Medina; Renato A. Martins; Ana Gabrielle Morais da Silva; Wesley J. Neely; Célio F. B. Haddad; Graziella V. DiRenzo; Alessandro Catenazzi; Rayna C. Bell; C. Guilherme Becker (Global Change Biology, 2025)
Shifting precipitation regimes driven by global climate change can alter vertebrate behavior and host‐symbiont relationships, potentially compromising host resistance to pathogen invasion. In Brazil's Atlantic Forest, a biodiversity hotspot, prior research identified drought as a key factor disrupting the skin microbiome, contributing to a die‐off of pumpkin toadlets due to the invasive waterborne fungal pathogen Batrachochytrium dendrobatidis (Bd). However, observational studies cannot disentangle the direct effect of moisture on Bd growth from increased amphibian activity during wet breeding seasons. Using field enclosures, we experimentally tested the influence of drought conditions on host microhabitat use, Bd disease dynamics, and the composition and predicted Bd‐inhibitory function of cutaneous bacterial communities. Each enclosure housed ecologically realistic densities of Brachycephalus pitanga , a micro‐endemic pumpkin toadlet. We simulated a short‐term drought in half of the enclosures using translucent tarp coverings. To track individual toadlets, we identified their unique markings and collected skin swabs biweekly over 3 months. We then implemented molecular techniques to quantify Bd loads and characterize skin bacterial diversity and composition over time. Our findings indicate that while drought may reduce overall Bd loads on hosts, this effect is partially offset by an increase in the use of water‐filled areas of the enclosures and by a disruption of the protective host skin microbiome. This study provides valuable insights into the cascading impacts of climate change on animal behavior, host‐symbiont interactions, and disease dynamics.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Comparison of salting-out assisted liquid-liquid extraction to polymeric solid phase extraction for liquid chromatography tandem mass spectrometry of neonicotinoids insecticides and metabolites in wastewater: Occurrence and aquatic risk assessment - Joyce Cristale; Raquel Wielens Becker; Valdemar Luiz Tornisielo; Renato Falcão Dantas; Shannon Bartelt-Hunt; Sathaporn Onanong; Daniel D. Snow (Environmental Pollution, 2025)

Production of bacterial protease via solid-state cultivation with agro-industrial by-products and eco-friendly perspectives of enzyme application - Carolina Becker da Silva; Gabriela Poll Moraes; Rubia Godoy Hoffmann; Tainara Lenz Goettems; Amanda Mendonça Azambuja; Daniel Joner Daroit (Clean Technologies and Environmental Policy, 2025)

Aquatic occurrence, fate and potential ecotoxicity of insecticide and fungicide residues originating from a biofuels production facility using pesticide-treated seeds - Jascika A.A. Maclean; Shannon Bartelt-Hunt; Daniel D. Snow; Josephus F. Borsuah; Raquel Wielens Becker; Moushumi Hazra (Journal of Hazardous Materials, 2025)

Stable isotope spatial patterns for the Southwest Atlantic Ocean towards polar waters - Luciana Riccialdelli; Samanta Dodino; Clara M. Iachetti; Santiago Favoretti; Daniel O. Bruno; Mónica A. Torres; Yamila A. Becker; Daniel A. Fernández; Andrea Raya Rey (Progress in Oceanography, 2024)

Developmental exposure of zebrafish to saxitoxin causes altered expression of genes associated with axonal growth - Neelakanteswar Aluru; Daniel P. Chapman; Kevin W. Becker; Benjamin A.S. Van Mooy; Sibel I. Karchner; John J. Stegeman; Mark E. Hahn (NeuroToxicology, 2024)

Evaluation of the effects of the Zika Virus-Immunoglobulin G+ complex on murine microglial cells - Laura da Silva Siqueira; Felipe Valle Fortes Rodrigues; Ângela Zanatta; João Ismael Budelon Gonçalves; Isadora Machado Ghilardi; Allan Marinho Alcará; Nicole Bernd Becker; Giulia Pinzetta; Gabriele Zanirati; Bruno Maestri Abrianos Becker; Helena Scartassini Erwig; Jaderson Costa da Costa; et al. (Journal of NeuroVirology, 2024)

The Ediacaran paleontological record in South America - Lucas V. Warren; Bruno Becker-Kerber; Lucas Inglez; Filipe G. Varejão; Luana P.C. Morais; Marcello G. Simões; Bernardo T. Freitas; Julia M. Arrouy; Lucía E. Gómez-Peral; Daniel G. Poiré; Juliana Okubo; Fabrício Caxito; et al. (Earth-Science Reviews, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Lipid biochemical diversity and dynamics reveal phytoplankton nutrient-stress responses and carbon export mechanisms in mesoscale eddies in the North Pacific Subtropical Gyre - Shavonna M. Bent; Daniel Muratore; Kevin W. Becker; Benedetto Barone; Tara Clemente; Helen F. Fredricks; Henry C. Holm; David M. Karl; Benjamin A. S. Van Mooy (Frontiers in Marine Science, 2024)
Mesoscale eddies cause deviations from the background physical and biogeochemical states of the oligotrophic oceans, but how these perturbations manifest in microbial ecosystem functioning, such as community macromolecular composition or carbon export, remains poorly characterized. We present comparative lipidomes from communities entrained in two eddies of opposite polarities (cyclone–anticyclone) in the North Pacific Subtropical Gyre (NPSG). A previous work on this two-eddy system has shown differences in particulate inorganic carbon (PIC) and biogenic silica sinking fluxes between the two eddies despite comparable total organic carbon fluxes. We measured the striking differences between the lipidomes of suspended and sinking particles that indicate taxon-specific responses to mesoscale perturbations. Specifically, cyanobacteria did not appear to respond to increased concentrations of phosphorus in the subsurface of the cyclonic eddy, while eukaryotic microbes exhibit P-stress relief as reflected in their lipid signatures. Furthermore, we found that two classes of lipids drive differences between suspended and sinking material: sinking particles are comparatively enriched in phosphatidylcholine (PC, a membrane-associated lipid) and triacylglycerol (TAG, an energy storage lipid). We observed significantly greater export of TAGs from the cyclonic eddy as compared to the anticyclone and found that this flux is strongly correlated with the concentration of ballast minerals (PIC and biogenic silica). This increased export of TAGs from the cyclone, but not the anticyclone, suggests that cyclonic eddy perturbations may be a mechanism for the delivery of energy-rich organic material below the euphotic zone.

Seawater softening by nanofiltration enables ecofriendly Dead Sea level stabilisation while creating the basis for cost-effective inland desalination - Daniel Janowitz; Nir Becker; Amer Sweity; Armin Margane; Nader Al Katheb; Sophie Groche; Süleyman Yüce; Thomas Wintgens (Desalination, 2024)

Biologically Important Areas II for cetaceans within U.S. and adjacent waters - West Coast Region - John Calambokidis; Michaela A. Kratofil; Daniel M. Palacios; Barbara A. Lagerquist; Gregory S. Schorr; M. Bradley Hanson; Robin W. Baird; Karin A. Forney; Elizabeth A. Becker; R. Cotton Rockwood; Elliott L. Hazen (Frontiers in Marine Science, 2024)
Here we update U.S. West Coast Biologically Important Areas (BIAs) that were published in 2015 using new data and approaches. Additionally, BIAs were delineated for two species that were not delineated in the 2015 BIAs: fin whales and Southern Resident killer whales (SRKW). While harbor porpoise BIAs remained the same, substantial changes were made for other species including identifying both larger overall areas (parent BIAs) and smaller core areas (child BIAs). For blue, fin, and humpback whales we identified, delineated, and scored BIAs using the overlap between the distribution and relative density from three data sources, leveraging the strengths and weaknesses of these approaches: 1) habitat density models based on Southwest Fisheries Science Center (SWFSC) line-transect data from systematic ship surveys conducted through 2018, 2) satellite tag data from deployments conducted by three research groups, and 3) sightings of feeding behavior from non-systematic effort mostly associated with small-boat surveys for photo-identification conducted by Cascadia Research Collective. While the previous BIAs were based solely on a more subjective assignment from only the small boat sightings, here we incorporate the other two data sources and use a more rigorous, quantitative approach to identify higher density areas and integrate the data types. This resulted in larger, better-supported, objective BIAs compared to the previous effort. Our methods are also more consistent with the delineation of BIAs in other regions. For SRKWs, the parent BIA was based on a modification of the Critical Habitat boundaries defined by the National Oceanographic and Atmospheric Administration (NOAA) and the Department of Fisheries and Oceans (DFO) Canada; a core BIA highlighting areas of intensified use was identified using both NOAA’s Critical Habitat and kernel density analyses of satellite tag data. Gray whale BIAs were re-evaluated for the migratory corridor of Eastern North Pacific gray whales, for Pacific Coast Feeding Group feeding areas, and for gray whales that feed regularly in Puget Sound.

Enzymatic processing of animal by-products: production of antioxidant hydrolysates with Bacillus sp. CL18 crude protease - Rubia Godoy Hoffmann; Gabriela Poll Moraes; Carolina Becker da Silva; Daniel Joner Daroit (Environmental Science and Pollution Research, 2024)

Nature 4.0: A networked sensor system for integrated biodiversity monitoring - Dirk Zeuss; Lisa Bald; Jannis Gottwald; Marcel Becker; Hicham Bellafkir; Jörg Bendix; Phillip Bengel; Larissa T. Beumer; Roland Brandl; Martin Brändle; Stephan Dahlke; Nina Farwig; et al. (Global Change Biology, 2024)
Ecosystem functions and services are severely threatened by unprecedented global loss in biodiversity. To counteract these trends, it is essential to develop systems to monitor changes in biodiversity for planning, evaluating, and implementing conservation and mitigation actions. However, the implementation of monitoring systems suffers from a trade‐off between grain (i.e., the level of detail), extent (i.e., the number of study sites), and temporal repetition. Here, we present an applied and realized networked sensor system for integrated biodiversity monitoring in the Nature 4.0 project as a solution to these challenges, which considers plants and animals not only as targets of investigation, but also as parts of the modular sensor network by carrying sensors. Our networked sensor system consists of three main closely interlinked components with a modular structure: sensors, data transmission, and data storage, which are integrated into pipelines for automated biodiversity monitoring. We present our own real‐world examples of applications, share our experiences in operating them, and provide our collected open data. Our flexible, low‐cost, and open‐source solutions can be applied for monitoring individual and multiple terrestrial plants and animals as well as their interactions. Ultimately, our system can also be applied to area‐wide ecosystem mapping tasks, thereby providing an exemplary cost‐efficient and powerful solution for biodiversity monitoring. Building upon our experiences in the Nature 4.0 project, we identified ten key challenges that need to be addressed to better understand and counteract the ongoing loss of biodiversity using networked sensor systems. To tackle these challenges, interdisciplinary collaboration, additional research, and practical solutions are necessary to enhance the capability and applicability of networked sensor systems for researchers and practitioners, ultimately further helping to ensure the sustainable management of ecosystems and the provision of ecosystem services.

Host functional traits as the nexus for multilevel infection patterns - Zheng Y.X. Huang; Fletcher W. Halliday; Daniel J. Becker (Trends in Ecology & Evolution, 2023)

Assessment of rapid wastewater surveillance for determination of communicable disease spread in municipalities - Mohsen Asadi; Daniel Hamilton; Corwyn Shomachuk; Femi F. Oloye; Chantel De Lange; Xia Pu; Charles A. Osunla; Jenna Cantin; Seba El-Baroudy; Edgard M. Mejia; Branden Gregorchuk; Michael G. Becker; et al. (Science of The Total Environment, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Functional traits explain waterbirds' host status, subtype richness, and community‐level infection risk for avian influenza - Shenglai Yin; Ning Li; Wenjie Xu; Daniel J. Becker; Willem F. de Boer; Chi Xu; Taej Mundkur; Nicholas M. Fountain‐Jones; Chunlin Li; Guan‐zhu Han; Qiang Wu; Diann J. Prosser; et al. (Ecology Letters, 2023)
Species functional traits can influence pathogen transmission processes, and consequently affect species' host status, pathogen diversity, and community‐level infection risk. We here investigated, for 143 European waterbird species, effects of functional traits on host status and pathogen diversity (subtype richness) for avian influenza virus at species level. We then explored the association between functional diversity and HPAI H5Nx occurrence at the community level for 2016/17 and 2021/22 epidemics in Europe. We found that both host status and subtype richness were shaped by several traits, such as diet guild and dispersal ability, and that the community‐weighted means of these traits were also correlated with community‐level risk of H5Nx occurrence. Moreover, functional divergence was negatively associated with H5Nx occurrence, indicating that functional diversity can reduce infection risk. Our findings highlight the value of integrating trait‐based ecology into the framework of diversity–disease relationship, and provide new insights for HPAI prediction and prevention.

Socio-oceanography: an opportunity to integrate marine social and natural sciences - Ekaterina Popova; Yevgeny Aksenov; Laurent O. Amoudry; Amani Becker; Lucy Bricheno; Jennifer M. Brown; Michael A. Clare; Alan Evans; Claire Evans; Sara E. Fowell; Svetlana Jevrejeva; Zoe Jacobs; et al. (Frontiers in Marine Science, 2023)
Marine natural sciences have been instrumental in helping society understand how ocean systems operate and the threats they face. However, there is a growing realisation that the societal challenges related to the marine environment can only be addressed through more effective integration with all aspects of social sciences. Nevertheless, to date, social sciences remain insufficiently integrated into marine research. Recognising historical weaknesses and drawing on the authors’ own experience of interdisciplinary research, albeit writing primarily from a natural marine science perspective, we propose a series of steps to promote integrated marine research inclusive of strong social science. We suggest that changing the perspectives and attitudes of natural scientists is key. The inherent interconnectivity between the ocean and society ensures that nearly everything we do in the marine natural sciences has the potential to influence and, perhaps address, ongoing and future societal challenges. Consequently, a key challenge for natural scientists is to recognise and communicate this in an accessible manner outside their own disciplines. To attempt to address these issues, we introduce the concept of “Socio-oceanography” which we define as an area of research that takes a “whole system” approach to the marine environment. It focuses on the challenges which require advancement of both natural and social science components, especially on those where the feedbacks between social and natural components are beginning to emerge. Here, we discuss its scope, challenges to its effective application and key steps to catalyse interdisciplinary approaches using this concept.

NT-CRISPR: Methode zur gentechnischen Veränderung von Vibrio natriegens - Daniel Stukenberg; Anke Becker (BIOspektrum, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Ecological conditions predict the intensity of Hendra virus excretion over space and time from bat reservoir hosts - Daniel J. Becker; Peggy Eby; Wyatt Madden; Alison J. Peel; Raina K. Plowright (Ecology Letters, 2023)
The ecological conditions experienced by wildlife reservoirs affect infection dynamics and thus the distribution of pathogen excreted into the environment. This spatial and temporal distribution of shed pathogen has been hypothesised to shape risks of zoonotic spillover. However, few systems have data on both long‐term ecological conditions and pathogen excretion to advance mechanistic understanding and test environmental drivers of spillover risk. We here analyse three years of Hendra virus data from nine Australian flying fox roosts with covariates derived from long‐term studies of bat ecology. We show that the magnitude of winter pulses of viral excretion, previously considered idiosyncratic, are most pronounced after recent food shortages and in bat populations displaced to novel habitats. We further show that cumulative pathogen excretion over time is shaped by bat ecology and positively predicts spillover frequency. Our work emphasises the role of reservoir host ecology in shaping pathogen excretion and provides a new approach to estimate spillover risk.

MOG-Specific T Cells Lead to Spontaneous EAE with Multilocular B Cell Infiltration in the GF-IL23 Model - Louisa Nitsch; Simon Petzinna; Julian Zimmermann; Daniel R. Getts; Albert Becker; Marcus Müller (NeuroMolecular Medicine, 2022)
Although IL-23 and downstream signal transduction play essential roles in neuroinflammation, the local impact of IL-23 in multiple sclerosis is still not fully understood. Our previous study revealed that the central nervous system (CNS)-restricted expression of IL-23 in a mouse model with astrocyte-specific expression of IL-23, called GF-IL23 mice, leads to spontaneous formation of infiltrates in the brain, especially in the cerebellum. To further investigate the impact of CNS-specific IL-23-expression on neuroinflammation, we studied the GF-IL23 model in mice expressing a myelin oligodendrocyte glycoprotein (MOG)-specific T cell receptor (GF23-2D2 mice). The GF23-2D2 mice developed a chronic progressive experimental autoimmune encephalomyelitis with myelitis and ataxia without requiring additional immunization. CNS-production of IL-23 alone induced pronounced neuroinflammation in the transgenic MOG-specific T cell receptor model. The GF23-2D2 mice spontaneously developed multilocular infiltrates with a high number of B cells, demyelination and a proinflammatory cytokine milieu indicating that the interaction of encephalitogenic T cells and B cells via co-stimulatory factors seemed to be crucial.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

NTRK2 gene fusions are uncommon in pilocytic astrocytoma - Daniel Antunes Moreno; Aline Paixão Becker; Cristovam Scapulatempo-Neto; Weder Menezes; Jamie Sheren; Aline M Walter; Carlos Clara; Hélio R. Machado; Ricardo S. Oliveira; Luciano Neder; Marileila Varella-Garcia; Rui Manuel Reis (Molecular Biology Reports, 2022)

Complex and flexible catabolism in Aromatoleum aromaticum pCyN1 - Patrick Becker; Annemieke Döhmann; Lars Wöhlbrand; Daniela Thies; Christina Hinrichs; Ramona Buschen; Daniel Wünsch; Meina Neumann‐Schaal; Dietmar Schomburg; Michael Winklhofer; Richard Reinhardt; Ralf Rabus (Environmental Microbiology, 2022)
Summary Large quantities of organic matter are continuously deposited, and (a)biotic gradients intersect in the soil–rhizosphere, where biodegradation contributes to the global cycles of elements. The betaproteobacterial genus Aromatoleum comprises cosmopolitan, facultative denitrifying degradation specialists. Aromatoleum aromaticum . pCyN1 stands out for anaerobically decomposing plant‐derived monoterpenes in addition to monoaromatic hydrocarbons, polar aromatics and aliphatics. The catabolic network's structure and flexibility in A . aromaticum pCyN1 were studied across 34 growth conditions by superimposing proteome profiles onto the manually annotated 4.37 Mbp genome. Strain pCyN1 employs three fundamentally different enzymes for C–H‐bond cleavage at the methyl groups of p ‐cymene/4‐ethyltoluene, toluene and p ‐cresol respectively. Regulation of degradation modules displayed substrate specificities ranging from narrow (toluene and cyclohexane carboxylate) via medium‐wide (one module shared by p ‐cymene, 4‐ethyltoluene, α‐phellandrene, α‐terpinene, γ‐terpinene and limonene) to broad (central benzoyl‐CoA pathway serving 16 aromatic substrates). Remarkably, three variants of ATP‐dependent (class I) benzoyl‐CoA reductase and four different β‐oxidation routes establish a degradation hub that accommodates the substrate diversity. The respiratory system displayed several conspicuous profiles, e.g. the presence of nitrous oxide reductase under oxic and of low‐affinity oxidase under anoxic conditions. Overall, nutritional versatility in conjunction with network regulation endow A . aromaticum pCyN1 with broad adaptability.

Subtle structures with not‐so‐subtle functions: A data set of arthropod constructs and their host plants - Cássio Cardoso Pereira; Samuel Novais; Milton Barbosa; Daniel Negreiros; Thiago Gonçalves‐Souza; Tomas Roslin; Robert Marquis; Nicholas Marino; Vojtech Novotny; Jerome Orivel; Shen Sui; Gustavo Aires; et al. (Ecology, 2022)
The construction of shelters on plants by arthropods might influence other organisms via changes in colonization, community richness, species composition, and functionality. Arthropods, including beetles, caterpillars, sawflies, spiders, and wasps often interact with host plants via the construction of shelters, building a variety of structures such as leaf ties, tents, rolls, and bags; leaf and stem galls, and hollowed out stems. Such constructs might have both an adaptive value in terms of protection (i.e., serve as shelters) but may also exert a strong influence on terrestrial community diversity in the engineered and neighboring hosts via colonization by secondary occupants. Although different traits of the host plant (e.g., physical, chemical, and architectural features) may affect the potential for ecosystem engineering by insects, such effects have been, to a certain degree, overlooked. Further analyses of how plant traits affect the occurrence of shelters may therefore enrich our understanding of the organizing principles of plant‐based communities. This data set includes more than 1000 unique records of ecosystem engineering by arthropods, in the form of structures built on plants. All records have been published in the literature, and span both natural structures (91% of the records) and structures artificially created by researchers (9% of the records). The data were gathered between 1932 and 2021, across more than 50 countries and several ecosystems, ranging from polar to tropical zones. In addition to data on host plants and engineers, we aggregated data on the type of constructs and the identity of inquilines using these structures. This data set highlights the importance of these subtle structures for the organization of terrestrial arthropod communities, enabling hypotheses testing in ecological studies addressing ecosystem engineering and facilitation mediated by constructs. There are no copyright restrictions and please cite this paper when using the data in publications.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

The macroecology and evolution of avian competence for Borrelia burgdorferi - Daniel J. Becker; Barbara A. Han (Global Ecology and Biogeography, 2021)
Aim Prediction of novel reservoirs of zoonotic pathogens would be improved by the identification of interspecific drivers of host competence (i.e., the ability to transmit pathogens to new hosts or vectors). Tick‐borne pathogens can provide a useful model system, because larvae become infected only when feeding on a competent host during their first blood meal. For tick‐borne diseases, competence has been studied best for Borrelia burgdorferi sensu lato ( Bb sl), which causes Lyme borreliosis. Major reservoirs include several small mammal species, but birds might play an under‐recognized role in human risk given their ability to disperse infected ticks across large spatial scales. Here, we provide a global synthesis of the ecological and evolutionary factors that determine the ability of bird species to infect larval ticks with Bb sl. Location Global. Time period 1983–2019. Major taxa studied Birds. Methods We compiled a dataset of Bb sl competence across 183 bird species and applied meta‐analysis, phylogenetic factorization and boosted regression trees to describe spatial and temporal patterns in competence, characterize its phylogenetic distribution across birds, reconstruct its evolution and evaluate the trait profiles associated with competent avian species. Results Half of the sampled bird species show evidence of competence for Bb sl. Competence displays moderate phylogenetic signal, has evolved multiple times across bird species and is pronounced in the genus Turdus . Trait‐based analyses distinguished competent birds with 80% accuracy and showed that such species have low baseline corticosterone, exist on both ends of the pace‐of‐life continuum, breed and winter at high latitudes and have broad migratory movements into their breeding range. We used these trait profiles to predict various likely but unsampled competent species, including novel concentrations of avian reservoirs within the Neotropics. Main conclusion Our results can generate new hypotheses for how birds contribute to the dynamics of tick‐borne pathogens and help to prioritize surveillance of likely but unsampled competent birds. Our findings also emphasize that birds display under‐recognized variation in their contributions to enzootic cycles of Bb sl and the broader need to consider competence in ecological and predictive studies of multi‐host pathogens.

Effect of Aerobic Physical Exercise in an Animal Model of Duchenne Muscular Dystrophy - Andreza Hoepers; Adriano Alberti; Viviane Freiberger; Letícia Ventura; Leoberto Ricardo Grigollo; Cristina Salar Andreu; Bruna Becker da Silva; Daniel Fernandes Martins; Rudy José Nodari Junior; Emilio L. Streck; Clarissa M. Comim (Journal of Molecular Neuroscience, 2020)

Expanding host specificity and pathogen sharing beyond viruses - Daniel J. Becker; Gregory F. Albery (Molecular Ecology, 2020)
Most emerging pathogens of humans can infect multiple host species (Woolhouse & Gowtage‐Sequeria, 2005). This simple fact has motivated multiple large‐scale, comparative analyses of the drivers of pathogen sharing and zoonotic pathogen richness among hosts as well as the factors determining the zoonotic potential of pathogens themselves. However, most of this work focuses on viruses, limiting a broader understanding of how host range varies within and between pathogen groups. In this issue of Molecular Ecology , Shaw et al. (2020) compile a comprehensive data set of host–pathogen associations across viruses and bacteria and test whether previous patterns observed in the former occur in the latter. They find most viruses and bacteria are specialists, and viruses are more likely to be generalists; however, generalist bacteria encompass multiple host orders, whereas viral sharing occurs more within host orders. Lastly, the authors demonstrate that many factors previously identified as predictors of zoonotic richness for viruses occur for bacteria and that host phylogenetic similarity is a primary determinant of cross‐species transmission. However, pathogen sharing with humans was more common and more weakly related to phylogenetic distance to Homo sapiens for bacteria compared to viruses, suggesting the former could pose greater spillover risks across host orders. This work represents a key advance in our understanding of host specificity and pathogen sharing beyond viruses.

Ecological and evolutionary drivers of haemoplasma infection and bacterial genotype sharing in a Neotropical bat community - Daniel J. Becker; Kelly A. Speer; Alexis M. Brown; M. Brock Fenton; Alex D. Washburne; Sonia Altizer; Daniel G. Streicker; Raina K. Plowright; Vladimir E. Chizhikov; Nancy B. Simmons; Dmitriy V. Volokhov (Molecular Ecology, 2020)
Most emerging pathogens can infect multiple species, underlining the importance of understanding the ecological and evolutionary factors that allow some hosts to harbour greater infection prevalence and share pathogens with other species. However, our understanding of pathogen jumps is based primarily around viruses, despite bacteria accounting for the greatest proportion of zoonoses. Because bacterial pathogens in bats (order Chiroptera) can have conservation and human health consequences, studies that examine the ecological and evolutionary drivers of bacterial prevalence and barriers to pathogen sharing are crucially needed. Here were studied haemotropic Mycoplasma spp. (i.e., haemoplasmas) across a species‐rich bat community in Belize over two years. Across 469 bats spanning 33 species, half of individuals and two‐thirds of species were haemoplasma positive. Infection prevalence was higher for males and for species with larger body mass and colony sizes. Haemoplasmas displayed high genetic diversity (21 novel genotypes) and strong host specificity. Evolutionary patterns supported codivergence of bats and bacterial genotypes alongside phylogenetically constrained host shifts. Bat species centrality to the network of shared haemoplasma genotypes was phylogenetically clustered and unrelated to prevalence, further suggesting rare—but detectable—bacterial sharing between species. Our study highlights the importance of using fine phylogenetic scales when assessing host specificity and suggests phylogenetic similarity may play a key role in host shifts not only for viruses but also for bacteria. Such work more broadly contributes to increasing efforts to understand cross‐species transmission and the epidemiological consequences of bacterial pathogens.

Demographic and environmental drivers of metagenomic viral diversity in vampire bats - Laura M. Bergner; Richard J. Orton; Julio A. Benavides; Daniel J. Becker; Carlos Tello; Roman Biek; Daniel G. Streicker (Molecular Ecology, 2020)
Viruses infect all forms of life and play critical roles as agents of disease, drivers of biochemical cycles and sources of genetic diversity for their hosts. Our understanding of viral diversity derives primarily from comparisons among host species, precluding insight into how intraspecific variation in host ecology affects viral communities or how predictable viral communities are across populations. Here we test spatial, demographic and environmental hypotheses explaining viral richness and community composition across populations of common vampire bats, which occur in diverse habitats of North, Central and South America. We demonstrate marked variation in viral communities that was not consistently predicted by a null model of declining community similarity with increasing spatial or genetic distances separating populations. We also find no evidence that larger bat colonies host greater viral diversity. Instead, viral diversity follows an elevational gradient, is enriched by juvenile‐biased age structure, and declines with local anthropogenic food resources as measured by livestock density. Our results establish the value of linking the modern influx of metagenomic sequence data with comparative ecology, reveal that snapshot views of viral diversity are unlikely to be representative at the species level, and affirm existing ecological theories that link host ecology not only to single pathogen dynamics but also to viral communities.

CNS-Specific Synthesis of Interleukin 23 Induces a Progressive Cerebellar Ataxia and the Accumulation of Both T and B Cells in the Brain: Characterization of a Novel Transgenic Mouse Model - Louisa Nitsch; Julian Zimmermann; Marius Krauthausen; Markus J. Hofer; Raman Saggu; Gabor C. Petzold; Michael T. Heneka; Daniel R. Getts; Albert Becker; Iain L. Campbell; Marcus Müller (Molecular Neurobiology, 2019)

Amphibian skin fungal communities vary across host species and do not correlate with infection by a pathogenic fungus - Daniel Medina; Myra C. Hughey; Jenifer B. Walke; Matthew H. Becker; Katherine Pontarelli; Shan Sun; Brian Badgley; Lisa K. Belden (Environmental Microbiology, 2019)
Summary Amphibian population declines caused by the fungus Batrachochytrium dendrobatidis (Bd) have prompted studies on the bacterial community that resides on amphibian skin. However, studies addressing the fungal portion of these symbiont communities have lagged behind. Using ITS1 amplicon sequencing, we examined the fungal portion of the skin microbiome of temperate and tropical amphibian species currently coexisting with Bd in nature. We assessed cooccurrence patterns between bacterial and fungal OTUs using a subset of samples for which bacterial 16S rRNA gene amplicon data were also available. We determined that fungal communities were dominated by members of the phyla Ascomycota and Basidiomycota, and also by Chytridiomycota in the most aquatic amphibian species. Alpha diversity of the fungal communities differed across host species, and fungal community structure differed across species and regions. However, we did not find a correlation between fungal diversity/community structure and Bd infection, though we did identify significant correlations between Bd and specific OTUs. Moreover, positive bacterial–fungal cooccurrences suggest that positive interactions between these organisms occur in the skin microbiome. Understanding the ecology of amphibian skin fungi, and their interactions with bacteria will complement our knowledge of the factors influencing community assembly and the overall function of these symbiont communities.

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

On the relationship between body condition and parasite infection in wildlife: a review and meta‐analysis - Cecilia A. Sánchez; Daniel J. Becker; Claire S. Teitelbaum; Paola Barriga; Leone M. Brown; Ania A. Majewska; Richard J. Hall; Sonia Altizer (Ecology Letters, 2018)
Body condition metrics are widely used to infer animal health and to assess costs of parasite infection. Since parasites harm their hosts, ecologists might expect negative relationships between infection and condition in wildlife, but this assumption is challenged by studies showing positive or null condition–infection relationships. Here, we outline common condition metrics used by ecologists in studies of parasitism, and consider mechanisms that cause negative, positive, and null condition–infection relationships in wildlife systems. We then perform a meta‐analysis of 553 condition–infection relationships from 187 peer‐reviewed studies of animal hosts, analysing observational and experimental records separately, and noting whether authors measured binary infection status or intensity. Our analysis finds substantial heterogeneity in the strength and direction of condition–infection relationships, a small, negative average effect size that is stronger in experimental studies, and evidence for publication bias towards negative relationships. The strongest predictors of variation in study outcomes are host thermoregulation and the methods used to evaluate body condition. We recommend that studies aiming to assess parasite impacts on body condition should consider host–parasite biology, choose condition measures that can change during the course of infection, and employ longitudinal surveys or manipulate infection status when feasible.

Incorporating Social Diversity into Wildfire Management: Proposing “Pathways” for Fire Adaptation - Travis B Paveglio; Matthew S Carroll; Amanda M Stasiewicz; Daniel R Williams; Dennis R Becker (Forest Science, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

De novo FBXO11 mutations are associated with intellectual disability and behavioural anomalies - Daniel Fritzen; Alma Kuechler; Mona Grimmel; Jessica Becker; Sophia Peters; Marc Sturm; Hela Hundertmark; Axel Schmidt; Martina Kreiß; Tim M. Strom; Dagmar Wieczorek; Tobias B. Haack; et al. (Human Genetics, 2018)

Projecting Marine Mammal Distribution in a Changing Climate - Gregory K. Silber; Matthew D. Lettrich; Peter O. Thomas; Jason D. Baker; Mark Baumgartner; Elizabeth A. Becker; Peter Boveng; Dorothy M. Dick; Jerome Fiechter; Jaume Forcada; Karin A. Forney; Roger B. Griffis; et al. (Frontiers in Marine Science, 2017)

Biotransformation of 2,4-toluenediamine in human skin and reconstructed tissues - Lisa Grohmann; Daniel Becker; Jörg Rademann; Nan Ma; Monika Schäfer-Korting; Günther Weindl (Archives of Toxicology, 2017)

Hydrogeologische Untersuchungen im oberflächennahen Opalinuston (Bohrloch Lausen, Schweiz) - Tobias Vogt; Uwe Hekel; Andreas Ebert; Jens K. Becker; Daniel Traber; Silvio Giger; Monika Brod; Christian Häring (Grundwasser, 2017)

Abundant collateralization of temporal lobe projections to the accumbens, bed nucleus of stria terminalis, central amygdala and lateral septum - Rhett A. Reichard; Suriya Subramanian; Mikiyas T. Desta; Tej Sura; Mary L. Becker; Comeron W. Ghobadi; Kenneth P. Parsley; Daniel S. Zahm (Brain Structure and Function, 2017)

Consensus Paper: Cerebellar Development - Ketty Leto; Marife Arancillo; Esther B. E. Becker; Annalisa Buffo; Chin Chiang; Baojin Ding; William B. Dobyns; Isabelle Dusart; Parthiv Haldipur; Mary E. Hatten; Mikio Hoshino; Alexandra L. Joyner; et al. (The Cerebellum, 2016)

Heterogeneity in patch quality buffers metapopulations from pathogen impacts - Daniel J. Becker; Richard J. Hall (Theoretical Ecology, 2016)

Willingness of Nonindustrial Private Forest Owners in Norway to Supply Logging Residues for Wood Energy - Hanne K. Sjølie; Dennis Becker; Daniel Håbesland; Birger Solberg; Berit Hauger Lindstad; Stephanie Snyder; Mike Kilgore (Small-scale Forestry, 2016)

Linking anthropogenic resources to wildlife–pathogen dynamics: a review and meta‐analysis - Daniel J. Becker; Daniel G. Streicker; Sonia Altizer (Ecology Letters, 2015)
Urbanisation and agriculture cause declines for many wildlife, but some species benefit from novel resources, especially food, provided in human‐dominated habitats. Resulting shifts in wildlife ecology can alter infectious disease dynamics and create opportunities for cross‐species transmission, yet predicting host–pathogen responses to resource provisioning is challenging. Factors enhancing transmission, such as increased aggregation, could be offset by better host immunity due to improved nutrition. Here, we conduct a review and meta‐analysis to show that food provisioning results in highly heterogeneous infection outcomes that depend on pathogen type and anthropogenic food source. We also find empirical support for behavioural and immune mechanisms through which human‐provided resources alter host exposure and tolerance to pathogens. A review of recent theoretical models of resource provisioning and infection dynamics shows that changes in host contact rates and immunity produce strong non‐linear responses in pathogen invasion and prevalence. By integrating results of our meta‐analysis back into a theoretical framework, we find provisioning amplifies pathogen invasion under increased host aggregation and tolerance, but reduces transmission if provisioned food decreases dietary exposure to parasites. These results carry implications for wildlife disease management and highlight areas for future work, such as how resource shifts might affect virulence evolution.

A longitudinal study of self-reported psychopathology in early ecstasy and amphetamine users - Daniel Wagner; Philip Koester; Benjamin Becker; Euphrosyne Gouzoulis-Mayfrank; Martin Hellmich; Joerg Daumann (Psychopharmacology, 2015)

Distinct dissolved organic matter sources induce rapid transcriptional responses in coexisting populations of P rochlorococcus , P elagibacter and the OM60 clade - Adrian K. Sharma; Jamie W. Becker; Elizabeth A. Ottesen; Jessica A. Bryant; Solange Duhamel; David M. Karl; Otto X. Cordero; Daniel J. Repeta; Edward F. DeLong (Environmental Microbiology, 2014)
Summary A considerable fraction of the E arth's organic carbon exists in dissolved form in seawater. To investigate the roles of planktonic marine microbes in the biogeochemical cycling of this dissolved organic matter ( DOM ), we performed controlled seawater incubation experiments and followed the responses of an oligotrophic surface water microbial assemblage to perturbations with DOM derived from an axenic culture of P rochlorococcus , or high‐molecular weight DOM concentrated from nearby surface waters. The rapid transcriptional responses of both P rochlorococcus and P elagibacter populations suggested the utilization of organic nitrogen compounds common to both DOM treatments. Along with these responses, both populations demonstrated decreases in gene transcripts associated with nitrogen stress, including those involved in ammonium acquisition. In contrast, responses from low abundance organisms of the NOR5/OM60 gammaproteobacteria were observed later in the experiment, and included elevated levels of gene transcripts associated with polysaccharide uptake and oxidation. In total, these results suggest that numerically dominant oligotrophic microbes rapidly acquire nitrogen from commonly available organic sources, and also point to an important role for carbohydrates found within the DOM pool for sustaining the less abundant microorganisms in these oligotrophic systems.

Interaction between prenatal stress and dopamine D4 receptor genotype in predicting aggression and cortisol levels in young adults - Arlette F. Buchmann; Katrin Zohsel; Dorothea Blomeyer; Erika Hohm; Sarah Hohmann; Christine Jennen-Steinmetz; Jens Treutlein; Katja Becker; Tobias Banaschewski; Martin H. Schmidt; Günter Esser; Daniel Brandeis; et al. (Psychopharmacology, 2014)

Memory-related hippocampal functioning in ecstasy and amphetamine users - Benjamin Becker; Daniel Wagner; Philip Koester; Katja Bender; Christoph Kabbasch; Euphrosyne Gouzoulis-Mayfrank; Jörg Daumann (Psychopharmacology, 2013)

Lysine biosynthesis in bacteria: a metallodesuccinylase as a potential antimicrobial target - Danuta M. Gillner; Daniel P. Becker; Richard C. Holz (JBIC Journal of Biological Inorganic Chemistry, 2013)

Potential of willow and its genetically engineered associated bacteria to remediate mixed Cd and toluene contamination - Nele Weyens; Kerim Schellingen; Bram Beckers; Jolien Janssen; Reinhart Ceulemans; Daniel van der Lelie; Safiyh Taghavi; Robert Carleer; Jaco Vangronsveld (Journal of Soils and Sediments, 2013)

Regulation of genes involved in nitrogen utilization on different C/N ratios and nitrogen sources in the model ectomycorrhizal fungus Hebeloma cylindrosporum - Meghan Avolio; Tobias Müller; Anja Mpangara; Michael Fitz; Ben Becker; Alexander Pauck; Anja Kirsch; Daniel Wipf (Mycorrhiza, 2012)

Mesenchymal stromal cells (MSCs): science and f(r)iction - Karen Bieback; Patrick Wuchter; Daniel Besser; Werner Franke; Matthias Becker; Michael Ott; Martin Pacher; Nan Ma; Christof Stamm; Harald Klüter; Albrecht Müller; Anthony D. Ho (Journal of Molecular Medicine, 2012)

Candidate Screening of the TRPC3 Gene in Cerebellar Ataxia - Esther B. E. Becker; Brent L. Fogel; Sanjeev Rajakulendran; Anna Dulneva; Michael G. Hanna; Susan L. Perlman; Daniel H. Geschwind; Kay E. Davies (The Cerebellum, 2011)

Pulmonary Gene Silencing in Transgenic EGFP Mice Using Aerosolised Chitosan/siRNA Nanoparticles - Ebbe J. B. Nielsen; Jan M. Nielsen; Daniel Becker; Alexander Karlas; Hridayesh Prakash; Sys Z. Glud; Jonathan Merrison; Flemming Besenbacher; Thomas F. Meyer; Jørgen Kjems; Kenneth A. Howard (Pharmaceutical Research, 2010)

Altered parahippocampal functioning in cannabis users is related to the frequency of use - Benjamin Becker; Daniel Wagner; Euphrosyne Gouzoulis-Mayfrank; Elmar Spuentrup; Jörg Daumann (Psychopharmacology, 2010)

Characteristics of human intestinal Escherichia coli with changing environments - David Skurnik; Daniel Bonnet; Claire Bernède‐Bauduin; Rémy Michel; Christian Guette; Jean‐Marie Becker; Corinne Balaire; Françoise Chau; Jacqueline Mohler; Vincent Jarlier; Jean‐Paul Boutin; Brigitte Moreau; et al. (Environmental Microbiology, 2008)
Summary To investigate if the characteristics of human intestinal Escherichia coli are changing with the environment of the host, we studied intestinal E. coli from subjects having recently migrated from a temperate to a tropical area. We determined the phylogenetic group, the prevalence of the antibiotic resistance, the presence of integrons and the strain diversity in faecal isolates from 25 subjects originally from metropolitan France and expatriated to French Guyana. These characteristics were compared with those of 25 previously studied Wayampi Amerindian natives of French Guyana and from 25 metropolitan French residents. The three groups of subjects were matched for age and sex, had not taken antibiotics for at least 1 month, nor had been hospitalized within the past year. In all, the characteristics of intestinal E. coli from Expatriates were intermediate between those found in residents from metropolitan France and those found in natives of French Guyana. Prevalence of carriage of resistant Gram‐negative bacteria in Expatriates was intermediate between French residents and Wayampi as were the prevalence of integrons in E. coli (12.3% versus 16.3% and 7.8% respectively), and the intra‐host diversity of E. coli (2.3 strains/subject versus 1.9 and 3.1, respectively); lastly, in Expatriates, the prevalence of carriage of phylogenetic group B2 strains was lower than in French residents (16% versus 56%, P = 0.005), while carriage of phylogenetic group A strains was lower than in Wayampi (56% versus 88%, P = 0.03). Our results suggest that the composition of the commensal intestinal flora of humans is not static but changes dynamically in response to new environmental conditions.

EST database for early flower development in California poppy (Eschscholzia californica Cham., Papaveraceae) tags over 6000 genes from a basal eudicot - John E. Carlson; James H. Leebens-Mack; P. Kerr Wall; Laura M. Zahn; Lukas A. Mueller; Lena L. Landherr; Yi Hu; Daniel C. Ilut; Jennifer M. Arrington; Stephanie Choirean; Annette Becker; Dawn Field; et al. (Plant Molecular Biology, 2006)

Erratum - Daniel J. Becker; Jay T. Myers; Melissa M. Ruff; Peter L. Smith; Brenda W. Gillespie; David W. Ginsburg; John B. Lowe (Mammalian Genome, 2003)

Strain-specific modification of lethality in fucose-deficient mice - Daniel J. Becker; Jay T. Myers; Melissa M. Ruff; Peter L. Smith; Brenda W. Gillespie; David W. Ginsburg; John B. Lowe (Mammalian Genome, 2003)

Stratospheric Photolysis Frequencies: Impact of an Improved Numerical Solution of the Radiative Transfer Equation - Gaby Becker; Jens-Uwe Grooss; Daniel S. McKenna; Rolf Müller (Journal of Atmospheric Chemistry, 2000)

The Upper Stratospheric Ozone Budget: An Update of Calculations Based on HALOE Data - Jens-Uwe Grooß; Rolf Müller; Gaby Becker; Daniel S. McKenna; Paul J. Crutzen (Journal of Atmospheric Chemistry, 1999)

Interaction of DNA-binding proteins with the 5′-flanking region of a cytokinin-responsive cucumber hydroxypyruvate reductase gene - Ge Jin; Maria C. Davey; John R. Ertl; Rui Chen; Zhu-tian Yu; Steven G. Daniel; Wayne M. Becker; Chong-maw Chen (Plant Molecular Biology, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Induction of tumor-specific cytotoxic T lymphocytes by immunization with autologous tumor cells and interleukin-2 gene transfected fibroblasts - Andreas Mackensen; Hendrik Veelken; Michael Lahn; Sebastian Wittnebel; Daniel Becker; Gabriele Köhler; Peter Kulmburg; Ulrich Brennscheidt; Felicia Rosenthal; Brigitte Franke; Roland Mertelsmann; A. Lindemann (Journal of Molecular Medicine, 1997)

Zur Beziehung zwischen endogener Atmung und Glucoseatmung bei Chlorella. - A. Pirson; A. L. Daniel; E. W. Becker (Archives of Microbiology, 1955)